2017
DOI: 10.1002/mame.201600448
|View full text |Cite
|
Sign up to set email alerts
|

Engineering 3D Aligned Nanofibers for Regulation of Cell Growth Behavior

Abstract: 3D aligned electrospun fibers hold a promising potential in a wide range of biomedical areas, including biosensors, controlled drug release, tissue engineering, etc. Thus, a cost‐effective and easy way to scale‐up fabrication for 3D aligned nanofibers is highly desired. Herein, a novel yet facile preparation process of 3D aligned nanofibers (3D AFs) by an improved electrospinning technique is reported. The obtained 3D AFs show enhanced controllability on morphology and fiber density, and thus facilitate adhesi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 33 publications
(21 citation statements)
references
References 48 publications
(54 reference statements)
0
21
0
Order By: Relevance
“…8, which demonstrated that the sorption of 3D CNTs-NFs was higher compared with most of previous reported sorbent [35,[38][39][40][41][42][43]. Although the adsorption property of the 3D CNTs-NFs was still lower compared with the graphene/CNT foam [44], the production of 3D CNTs-NFs is simple and cost effective. More importantly, its fabrication can be scaled-up.…”
Section: Analysis Of Adsorption Propertiesmentioning
confidence: 77%
“…8, which demonstrated that the sorption of 3D CNTs-NFs was higher compared with most of previous reported sorbent [35,[38][39][40][41][42][43]. Although the adsorption property of the 3D CNTs-NFs was still lower compared with the graphene/CNT foam [44], the production of 3D CNTs-NFs is simple and cost effective. More importantly, its fabrication can be scaled-up.…”
Section: Analysis Of Adsorption Propertiesmentioning
confidence: 77%
“…BMSCs were then seeded into/onto each 3D HA/PAN composite scaffold and HA/PAN composite membrane at a density of 1.0 Â 10 4 cells per well according to previous method. 38,39 Aer 2 h cell attachment, 0.5 ml complete culture medium was added into each well. The resulting substrates/cell constructs were cultured in an incubator at 37 C, 95% relative humidity and 5% CO 2 partial pressure.…”
Section: Cell Seedingmentioning
confidence: 99%
“…Electrospinning technology [ 18 , 19 ] has the advantages of simple preparation equipment, low spinning cost, and controllable process, and has become one of the main ways to effectively prepare nanofibers. By changing the receiving device of electrospinning, controlling the electric field, and including an additional magnetic field, we can obtain different forms of aligned nanofiber assemblies including oriented nanofiber membranes, oriented nanofiber bundles, and oriented nanofiber coated yarns, which will further expand the application field of directional nanofiber [ 20 , 21 , 22 , 23 , 24 , 25 ].…”
Section: Introductionmentioning
confidence: 99%